Efektivitas Penerapan Aplikasi Mobile Identitas Kependudukan Digital Dalam Meningkatkan Pelayanan Publik di Kantor Dinas Kependudukan dan Catatan Sipil Kabupaten Subang - Sulistia, Tania; Setiarani, R. Aulia Bunga; Rofi, Abdul; Nisa, Rani Attakun; Natika, Luki (The World of Public Administration Journal, 2024)
This study evaluates the implementation of the Digital Population Identity (IKD) mobile application as an effort to improve the quality of public services at the Population and Civil Registry Office (Disdukcapil) of Subang Regency. With rapid technological advancements, public service digitalization has become a priority for increasing efficiency and accessibility in population administration. The IKD application was introduced to facilitate public access to Disdukcapil services, reduce waiting times, and streamline administrative processes. This study adopts Steers’ theoretical approach, examining effectiveness through the analysis of organizational characteristics, external environment, workforce, and management policies and practices. Using a qualitative research method through interviews and field observations, the study identifies several challenges in the implementation of IKD, including limited public understanding of technology and the technical readiness of Disdukcapil to address technical obstacles. The findings are expected to contribute to the development of optimal technology adaptation and communication strategies to enhance the acceptance and effectiveness of the IKD application, supporting a more responsive and inclusive transformation of digital-based public services.